Trust in Tourism and Travel Decision-Making: A Systematic Review of Consumer Behavior Perspectives - Darmawi Darmawi; Anni faridah; Yuliana Yuliana; Kasmita Kasmita (Brilliant International Journal Of Management And Tourism, 2026)
This study systematically reviews the role of trust in tourism and travel decision-making from a consumer behavior perspective. Although studies on trust in tourism have increased, the relationship between trust, perceived risk, satisfaction, and loyalty remains fragmented and lacks conceptual integration. Using a Systematic Literature Review (SLR) approach with the PRISMA framework, this study identified and synthesized relevant articles from Scopus, Web of Science, and ScienceDirect published between 2015 and 2025. The selected studies were analyzed through descriptive and thematic analysis to examine the development, determinants, and implications of trust in tourism contexts. The findings show that trust has evolved into a multidimensional concept consisting of cognitive, affective, social, and digital (e-trust) dimensions. Trust plays an important role in reducing perceived risk and strongly influences tourists’ decision-making, satisfaction, and loyalty. Key determinants of trust include service quality, destination reputation, information credibility, online reviews, and system security. However, the literature still lacks integrative frameworks and relies heavily on fragmented empirical approaches. This study offers a holistic understanding of trust and highlights research gaps, especially regarding the integration of offline and digital tourism contexts, while emphasizing the need for more comprehensive trust models in tourism.